Zinc acetylacetonate doping for enhanced cathode interface layer in organic solar cells. (15th December 2022) - Wang, Wei; Lin, Zhichao; Li, Xin; Tang, Yirong; Zhong, Wentao; Zhang, Chunhui; Yang, Tingbin; Liang, Yongye
Abstract : Zinc acetylacetonate is introduced to dope PDINO as an efficient cathode interface layer, affording higher power conversion efficiency and less sensitivity to CIL thickness for organic solar cells. Abstract : Interface engineering is a necessary process to achieve enhanced device performance in organic solar cells (OSCs). Herein, we report a facile and low-cost approach using zinc acetylacetonate (ZnAcac, ZAA) to dope perylene diimides functionalized with amino oxide (PDINO) as an improved cathode interface layer (CIL) for OSCs. In contrast to the pristine PDINO CIL, the PDINO + ZAA CIL exhibit lower electron affinity level and improved conductivity due to electron transfer between PDINO and ZAA. As a result, OSCs with PDINO + ZAA CIL deliver higher power conversion efficiencies (PCEs) and exhibit less efficiency decay with thicker CIL than the OSCs with PDINO CIL. With 10 nm PDINO + ZAA as the CIL, the typical PM6:BTP-eC9 OSCs can achieve an enhanced average PCE of 17.1% than PDINO OSC (16.4%), mainly due to less charge recombination and improved charge extraction and transport ability in devices. A good PCE of 15.4% can be still maintained with 70 nm CIL. Our results prove that PDINO + ZAA is a high-quality CIL and provide a simple and low-cost interface engineering strategy to optimize the CILs in OSCs.